A fronto-insular-parietal network for the sense of body ownership. (2nd March 2022) - Moro, Valentina; Pacella, Valentina; Scandola, Michele; Besharati, Sahba; Rossato, Elena; Jenkinson, Paul M; Fotopoulou, Akaterini
Abstract: Neuropsychological disturbances in the sense of limb ownership provide unique opportunities to study the neurocognitive basis of body ownership. Previous small sample studies that showed discrete cortical lesions cannot explain why multisensory, affective, and cognitive manipulations alter disownership symptoms. We tested the novel hypothesis that disturbances in the sense of limb ownership would be associated not only with discrete cortical lesions but also with disconnections of white-matter tracts supporting specific functional networks. We drew on an advanced lesion-analysis and Bayesian statistics approach in 49 right-hemisphere patients (23 with and 26 without limb disownership). Our results reveal that disturbances in the sense of ownership are associated with lesions in the supramarginal gyrus and disconnections of a fronto-insular-parietal network, involving the frontal-insular and frontal inferior longitudinal tracts, confirming previous disconnection hypotheses. Together with previous behavioral and neuroanatomical results, these findings lead us to propose that the sense of body ownership involves the convergence of bottom-up, multisensory integration, and top-down monitoring of sensory salience based on contextual demands.